Basic perspective drawing : a visual approach - Montague, John. (Hoboken, New Jersey : Wiley, 2013)
Basic Perspective Drawing introduces students, both those in formal design courses and self-learners, to the basic principles and techniques of perspective drawing. Clear and accessible illustrations show how to construct perspective views one step at a time. The new, streamlined Sixth Edition contains must-have content for students and instructors in art and design, architecture, and interior design programs. Updated illustrations reflect the most current drawing styles and examples while supplementary tutorial videos, grouped by architectural disciplines, interior design, and studio art/illustration, provide live-action demonstrations of key topics discussed in the book.
Overview -- Rendering perspective views from observed reality -- Plans, elevations, and paraline projections -- Constructing perspective views -- Geometric tools: diagonals, squares, and cubes -- Sloping planes and surfaces -- Circles and curved surfaces -- Shadows and reflections -- Freehand sketching and rapid visualization -- The figure in perspective -- Shading and rendering -- Aerial perspective -- Appendix A: examples of perspective views -- Appendix B: notes on studying and teaching perspective drawing -- Index.
Includes index.
Keywords: PERSPECTIVE